2020
DOI: 10.1007/s42452-020-03738-3
|View full text |Cite
|
Sign up to set email alerts
|

Examination of potential impacts of future climate change on solar radiation in Togo, West Africa

Abstract: This study investigates the potential impacts of future warming on Global Solar Radiation (GSR) in different parts of Togo, West Africa. It used regional climate simulations of the International Centre for Theoretical Physics version 4.7 (RegCM4) driven by HadGEM-ES and NorESM-M GCM for three different time-slice periods: baseline , near future (2031-2060) and far future . The models produced realistic simulations of GSR and temperature characteristics over the stations and the simulations spread are within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Fant et al [48] projected small changes in solar PV generation in 2050, with an increase in the winter and a decrease in the summer in most regions of Southern Africa. Patchali et al [49] also reported reductions in global solar radiation at several locations in Togo, West Africa. Ohunakin et al [50] showed a decrease in global solar radiation in Nigeria, with the largest possible decrease in southern Nigeria.…”
Section: Effects Of Hargreaves-samani (Hs) Coefficient On Climate For...mentioning
confidence: 94%
“…Fant et al [48] projected small changes in solar PV generation in 2050, with an increase in the winter and a decrease in the summer in most regions of Southern Africa. Patchali et al [49] also reported reductions in global solar radiation at several locations in Togo, West Africa. Ohunakin et al [50] showed a decrease in global solar radiation in Nigeria, with the largest possible decrease in southern Nigeria.…”
Section: Effects Of Hargreaves-samani (Hs) Coefficient On Climate For...mentioning
confidence: 94%
“…Table 1 shows the typical monthly values of global SR over Sohag Al Gadida City [32]. The chart shows that there are a lot of SE events at this location, particularly in the summer, when the mean daily SR in June was 8.13 kWh/m 2 /day [33,34]. Moreover, Figure 6 displays the monthly mean of the horizontal radiation for 22 years.…”
Section: Sr Data For the Sitementioning
confidence: 99%
“…Their results indicated a 2% decrease in PVP over the African continent in the mid-century under RCP8.5 [50]. Other authors investigated the impacts of future global warming on solar irradiance using RegCM4 driven by two global climate models (GCMs) at a 25 km resolution run under RCP2.6 and 8.5 [51]. This study was conducted over five selected Togolese cities across the five regions.…”
Section: Introductionmentioning
confidence: 99%